Covalent organic framework composite polyphenyl ether anion exchange membrane and preparation method thereof
By introducing a covalent organic frame composite polyphenylene ether structure and alkyl linkage COF-TpBpy framework in anion exchange membrane, the problem of difficult balance between ionic conductivity and mechanical properties of existing membranes is solved, and high conductivity is achieved The combination of rate and good mechanical properties and improves the chemical and thermodynamic stability of the membrane.
Patent Information
- Application Number
- CN202411387673.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-06
AI Technical Summary
The existing anion exchange membranes are difficult to achieve a balance between ionic conductivity and mechanical properties, and are easily attacked by nucleophilic substances under alkaline conditions, resulting in structural damage, resulting in low conductivity and insufficient stability.
The structure of a covalent organic frame composite polyphenylene ether anion exchange membrane is adopted, and the ion conduction capacity of the membrane is enhanced by introducing an alkyl-linked COF-TpBpy framework on the COFs frame as a filler, and the conductance of the membrane is enhanced by quaternary amination modification. sex.
The ionic conductivity and mechanical properties of the anion exchange membrane are significantly improved, the chemical stability and thermodynamic stability of the membrane are enhanced, and the hydrolysis resistance under alkaline conditions is improved.
Smart Images

Figure CN119410122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new energy materials and relates to a membrane material, in particular to an anion exchange membrane based on a covalent organic framework structure and a preparation method thereof. Background Art
[0002] Global energy use continues to increase, energy service costs continue to rise, and energy supply, climate and local air quality have all been negatively affected. In order to meet the needs of sustainable development, hydrogen energy, as a recognized low-carbon and zero-carbon energy, has received widespread attention.
[0003] Hydrogen production by water electrolysis can produce green hydrogen with zero carbon emissions, which meets the needs of global energy development. In addition, water electrolysis hydrogen production technology is reliable, simple to operate, easy to maintain, pollution-free, and has high hydrogen purity. It is a mature technology with good development prospects. On the technical level, water electrolysis hydrogen production technology uses low-cost non-precious metal catalysts and efficient and stable anion exchange membranes (AEMs), which can significantly reduce the cost of key raw materials.
[0004] However, the AEMs currently used have not yet reached the ideal state in some key characteristics, and their efficiency and stability still need to be improved.
[0005] The challenges faced by AEMs mainly come from the following two aspects: On the one hand, improving ionic conductivity can improve the hydrogen production efficiency of the electrolyzer, but this process will increase the water absorption and swelling rate of the membrane, reducing the mechanical properties and stability of the membrane. Therefore, it is urgent to solve the trade-off between ionic conductivity and membrane mechanical properties; on the other hand, the ether bonds and ester bonds contained in the main chain of AEMs and the cationic groups such as amino groups and quaternary ammonium salts in the side chains are easily oxidized by OH groups under alkaline conditions. - The cationic groups and the polymer main chain are easily attacked by nucleophilic OH and hydrolyzed, resulting in the breakage of the membrane molecular chain and the detachment of the ion exchange group. - The problem of attack by substances such as ions is one of the important topics in the research and development of alkaline anion exchange membranes.
[0006] Low conductivity is one of the main challenges facing AEMs, which directly affects the current efficiency and energy consumption of the electrolyzer and is a limiting factor in improving the efficiency of hydrogen production in the current electrolyzer. An effective way to increase ionic conductivity is to optimize the AEMs polymer matrix, increase ion migration channels by introducing conductive fillers, adjust the membrane structure to optimize the ion migration path, and develop AEMs with high conductivity and good mechanical properties.
[0007] Covalent organic frameworks (COFs) use strong bonds to connect molecular components into a predetermined periodic structure, and have good pore structure, chemical stability and thermodynamic stability, which make them potential in separating and transporting small molecules. Therefore, constructing COFs "ion channel" nanostructures in the AEMs structure for assisted transport can make AEMs have both good ion selectivity and low water absorption and swelling rate.
[0008] Although COFs have made a lot of progress in the application of membrane materials, there are still problems that need to be solved. For example, the lack of sufficient conductive sites on the surface of COFs has restricted its development in AEMs. Surface modification of COFs to improve their performance is a very effective strategy to improve the ionic conductivity of AEMs.
[0009] Fengxiang Zhang et al. (Mixed matrix anion exchange membrane containing covalent organic frameworks: Ultra-low IEC but medium conductivity. Applied Surface Science , 2021, 560, 0169-4332.) A quaternary ammonium COF (QCOF) was synthesized by a mechanochemical method and combined with a hydroxyl-functionalized polysulfone matrix to prepare a mixed matrix AEMs (or MMAEMs) with rich hydrogen bond networks and micropores. The synergistic effect enhanced the conductivity of the hydroxide, with an ion exchange capacity (IEC) of 0.38 mmol / g and a swelling rate of 2.5% at a QCOF content of 20%. However, the conductivity of the MMAEMs at 30°C was only 14.3 mS cm -1 This is related to the fact that the side chains of the COFs framework have not been modified with diversified functions, which results in low electrical conductivity and limits its use in devices.
[0010] Side chain functionalization modification is one of the effective methods to improve the electrical conductivity of COFs. By introducing diverse functional groups that can promote hydroxide conduction on the side chains of COFs, their electrical conductivity can be enhanced, thereby enhancing their performance in applications such as energy storage and conversion. Summary of the invention
[0011] The purpose of the present invention is to provide a covalent organic framework composite polyphenylene ether anion exchange membrane and a preparation method thereof, by improving the ion conductivity of the COFs framework, further enhancing the migration channels and paths of ions, improving the transmission performance of AEMs, and providing a more efficient solution for applications such as electrolysis of water to produce hydrogen.
[0012] The covalent organic framework composite polyphenylene ether anion exchange membrane of the present invention is an organic film composed of a quaternary ammonium polyphenylene ether represented by the following structural formula (I) as a film matrix, and a COF-TpBpy framework grafted with an alkyl chain represented by the following structural formula (II) as a filler, wherein the mass percentage of the film matrix is 95-99%, and the mass percentage of the filler is 1-5%.
[0013]
[0014]
[0015] The quaternized polyphenylene ether shown in the structural formula (I) is a copolymer QAPPO composed of quaternized polyphenylene ether structural units and polyphenylene ether structural units obtained by the quaternization reaction of polyphenylene ether, and the molar ratio of the quaternized polyphenylene ether structural units is x =0.4~0.5.
[0016] The alkyl chain grafted COF-TpBpy framework shown in structural formula (II) is used as an ion channel and is abbreviated as QAxSLCOF-TpBpy. Furthermore, the covalent organic framework composite polyphenylene ether anion exchange membrane of the present invention is abbreviated as QAxSLCOF-TpBpy@PPO, wherein x represents different R groups.
[0017] Specifically, the R is C 1~3 Alkyl or fluorine-substituted alkyl.
[0018] More specifically, the fluorine substitution may be monofluorine substitution, polyfluorine substitution or perfluorine substitution.
[0019] In the QAxSLCOF-TpBpy ion channel of the present invention, the R group iodide acts as a nucleophilic reagent to attack the nitrogen atom (N site) on the pyridine ring to generate a nucleophilic substitution reaction, and the R group is connected to the nitrogen atom through a chemical bond, so that the nitrogen atom carries a positive charge, forming N + cation; at the same time, the iodine atom is separated and forms an iodide ion (I - ), around the positively charged N + Create a stable environment.
[0020] Nanostructured COF-TpBpy ion channels are used in the QAxSLCOF-TpBpy@PPO membrane of the present invention. Based on the advantages of large specific surface area, adjustable pore size and structure, convenient function customization, and flexible covalent combination of building units, a highly arranged and directional ion channel structure can be obtained in the matrix membrane.
[0021] Furthermore, as a polymer with excellent mechanical properties and chemical stability, the toughness of QAPPO can be combined with the rigid structure of the QAxSLCOF-TpBpy ion channel to achieve the enriched state of the QAxSLCOF-TpBpy rigid structure transport track, thereby forming a high-performance mixed matrix membrane with rich ion transport channels to enhance its ion conductivity.
[0022] Furthermore, the present invention also provides a method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane, which comprises dissolving brominated polyphenylene ether (BPPO) represented by structural formula (III) in a well-soluble solvent thereof, adding a required amount of COF-TpBpy framework grafted with an alkyl chain represented by structural formula (II), and introducing trimethylamine to carry out quaternary amination reaction after uniform dispersion. After the reaction solution forms a film and is dried, the anion exchange membrane is prepared.
[0023]
[0024] Wherein, the brominated polyphenylene ether is a copolymer composed of brominated polyphenylene ether structural units and polyphenylene ether structural units, and the molar ratio of the brominated polyphenylene ether structural units is x =0.4~0.5.
[0025] In more detail, the well-soluble solvent for the brominated polyphenylene ether can be any organic solvent that has good solubility and stability for the brominated polyphenylene ether, and the present invention has no particular limitation thereto.
[0026] Preferably, the well-soluble solvent described in the present invention may be N-methylpyrrolidone or dimethylformamide.
[0027] In more detail, the present invention is to prepare the covalent organic framework composite polyphenylene ether anion exchange membrane after spreading the reaction solution after the quaternization reaction, placing it under vacuum conditions at 80°C for not less than 30 hours, and slowly drying the solvent and unreacted trimethylamine. The thickness of the membrane is controlled to be about 60±5μm.
[0028] Furthermore, the present invention also provides a typical preparation method of the COF-TpBpy framework grafted with alkyl chains as filler, which is to use the covalent organic framework material COF-TpBpy as a raw material, and to carry out an iodination reaction with an iodide of structural formula RI in a benign dispersing solvent thereof to obtain a COF-TpBpy framework grafted with alkyl chains of different structures.
[0029] Where R is C 1~3 The alkyl group or the fluorine-substituted alkyl group may be monofluorine-substituted, polyfluorine-substituted or perfluorine-substituted.
[0030] More specifically, the covalent organic framework material COF-TpBpy described in the present invention can be COF-TpBpy prepared by various reported preparation methods, and the present invention has no special limitation thereto.
[0031] However, preferably, the COF-TpBpy of the present invention can be an ion channel COF-TpBpy structure obtained by condensing trialdehyde phloroglucinol and 5,5'-diamino-2,2'-bipyridine as raw materials in an N,N-dimethylaniline / 1,2-dichlorobenzene solvent system of acetic acid aqueous solution.
[0032] Specifically, the molar ratio of trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is preferably 1:1.5-2.
[0033] Furthermore, the present invention also performs ultrasonic refinement treatment on the COF-TpBpy, specifically, the covalent organic framework material COF-TpBpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and the suspension is crushed using an ultrasonic cell crusher, and the solvent is removed and dried to obtain a refined SLCOF-TpBpy material. The SLCOF-TpBpy material after refinement treatment is more conducive to the subsequent iodination reaction to graft alkyl chains.
[0034] The present invention adopts the above-mentioned ultrasonic fragmentation method to assist in achieving high dispersibility and encapsulation of QAxSLCOF-TpBpy, thereby further improving the controllability of ion channel arrangement and transport sites in the membrane.
[0035] The present invention innovatively introduces ion channels with highly arranged transport sites and multiple cationic sites into polyphenylene ether to synthesize a new type of covalent organic framework composite polyphenylene ether anion exchange membrane, which not only has excellent structural stability, but also significantly improves OH - The ionic conductivity of the material shows great potential in high-performance ion conduction channel structures.
[0036] The covalent organic framework composite polyphenylene ether anion exchange membrane of the present invention has a simple preparation method, low cost, and relatively superior electrochemical performance, and can be used in alkaline fuel cells, carbon dioxide reduction and water electrolysis devices, and has broad application prospects.
[0037] QAxSLCOF-TpBpy has a highly ordered pore structure. By introducing this material, the pore structure and functional groups of the matrix membrane can be adjusted, thereby improving the ion transport performance of the matrix membrane. At the same time, based on the high chemical stability and thermodynamic stability of QAxSLCOF-TpBpy, the acid and alkali resistance, high temperature resistance and other properties of the matrix membrane can be enhanced, thereby improving its chemical stability. In addition, the intrinsic characteristics of the rigid structure of QAxSLCOF-TpBpy can also enable AEMs to maintain a low water absorption and swelling rate while improving ion conduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the H NMR spectrum of brominated polyphenylene ether (BPPO).
[0039] Figure 2 This is the H NMR spectrum of polyphenylene ether anion exchange membrane (QAPPO) and the H NMR spectrum of brominated polyphenylene ether (BPPO).
[0040] Figure 3 This is a comparison chart of the infrared spectra of SLCOF-TpBpy and QAxSLCOF-TpBpy with different structures.
[0041] Figure 4 This is a comparison chart of infrared spectra of QAPPO, SLCOF-TpBpy@PPO and QAxSLCOF-TpBpy@PPO films with different structures.
[0042] Figure 5 This is the IEC comparison curve of QAPPO, SLCOF-TpBpy@PPO and QAxSLCOF-TpBpy@PPO films with different structures.
[0043] Figure 6 This is the relationship curve between ionic conductivity and temperature of QAPPO, SLCOF-TpBpy@PPO and QAxSLCOF-TpBpy@PPO membranes with different structures.
[0044] Figure 7 This is a comparison curve of the water absorption of QAPPO and QAxSLCOF-TpBpy@PPO membranes.
[0045] Figure 8 It is a comparison curve of the swelling ratio of QAPPO and QAxSLCOF-TpBpy@PPO membranes.
[0046] Fig. 9 This is a comparison curve of the mechanical properties of QAPPO, COF-TpBpy@PPO, QAmSLCOF-TpBpy@PPO and QAmCOF-TpBpy@PPO membranes. Implementation
[0047] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0048] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0049] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0050] The covalent organic framework composite polyphenylene ether anion exchange membrane of the present invention is specifically prepared according to the following method:
[0051] Under inert protection, polyphenylene ether, N-bromosuccinimide and azobisisobutyronitrile were reacted in a chlorobenzene solvent system to prepare brominated polyphenylene ether (BPPO).
[0052] The ion channel COF-TpBpy structure was synthesized by condensation reaction of trialdehyde phloroglucinol and 5,5'-diamino-2,2'-bipyridine in a mixed solution system of N,N-dimethylaniline / 1,2-dichlorobenzene;
[0053] COF-TpBpy is ground and ultrasonically crushed to obtain refined SLCOF-TpBpy, which is dispersed in an N-methylpyrrolidone or dimethylformamide solvent system, and alkylating agents of different structures are added under inert protection to obtain a rigid ion channel QAxSLCOF-TpBpy having a structure shown in structural formula (II) through grafting reaction;
[0054] A required amount of QAxSLCOF-TpBpy is added to a brominated polyphenylene ether solvent system, and trimethylamine is used to carry out a quaternization reaction to obtain a mixed membrane homogeneous solution;
[0055] The formed homogeneous solution is poured onto a clean glass plate and slowly dried to prepare the covalent organic framework composite polyphenylene ether anion exchange membrane of the present invention.
[0056] Specifically, polyphenylene ether, N-bromosuccinimide and azobisisobutyronitrile are dissolved in chlorobenzene, and refluxed at 135-140° C. to prepare brominated polyphenylene ether.
[0057] More specifically, the molar ratio of polyphenylene ether to N-bromosuccinimide in the reflux reaction is 1:3.
[0058] Furthermore, the dried polyphenylene ether is preferably dissolved in chlorobenzene at a concentration of 6.5% (w / v); and the reflux reaction time is preferably 6 to 7 hours.
[0059] The product obtained by the reflux reaction is washed with methanol and then air-dried to obtain brominated polyphenylene ether.
[0060] Specifically, in the condensation reaction, the molar ratio of the raw materials trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is 1:1.5.
[0061] More specifically, 6 mol / L acetic acid aqueous solution is also added into the condensation reaction system.
[0062] After the condensation reaction is completed, the precipitate is collected by centrifugation and dried in vacuum at 80° C. to obtain the ion channel COF-TpBpy structure.
[0063] Furthermore, the present invention grinds the obtained COF-TpBpy for 2 hours, disperses it in a solvent, and uses an ultrasonic cell disruptor with a power of 100 to 200 W to disrupt it to obtain SLCOF-TpBpy. The preferred disruption time is 1.5 to 2 hours.
[0064] More preferably, the suspension may be cooled during the crushing process to maintain the temperature of the suspension at about 30°C.
[0065] The grafting reaction requires the dropwise addition of an alkylating agent and is carried out under inert protection and light-proof conditions.
[0066] Furthermore, the grafting reaction time is preferably 24 to 30 hours.
[0067] Preferably, in the present invention, the brominated polyphenylene ether is fully dissolved in a solvent to obtain a 2% (w / v) solution for quaternization reaction.
[0068] Specifically, the present invention is to place the quaternary amination reaction product under vacuum conditions at 80°C for 30 hours after film laying, slowly dry the solvent and unreacted trimethylamine, and prepare a covalent organic framework composite polyphenylene ether anion exchange membrane with a membrane thickness controlled at about 60±5μm. Example
[0069] Example 1
[0070] Under argon protection, polyphenylene ether (1.8 g, 15 mmol, Mn = 50000-58000), N-bromosuccinimide (1.3623 g, 7.65 mmol) and azobisisobutyronitrile (0.0753 g, 0.46 mmol) were dissolved in 28 mL of chlorobenzene and refluxed at 135 °C for 6 h.
[0071] After the reaction solution cooled to room temperature, it was slowly added dropwise into 20 mL of methanol with continuous ultrasound to precipitate the reactants to prevent agglomeration.
[0072] The precipitate was washed repeatedly with methanol (10×4 mL), and the washed product was placed in a 50° C. forced air drying oven and dried overnight to obtain brominated polyphenylene ether (BPPO), and the detected bromination rate reached 40-50%.
[0073] The prepared BPPO was subjected to nuclear magnetic resonance analysis and obtained Figure 1 The hydrogen spectrum shown in Figure 1 shows the hydrogen atom signals on the benzene ring appear around 6.6 ppm, marked as a and b. Due to the presence of the bromine substituent, the two hydrogen atoms originally at the meta position on the benzene ring are no longer equivalent, resulting in them being 1 The signal positions in the H NMR spectrum are different. In addition, the signal at 2.09 ppm (c) is attributed to the hydrogen atom on the benzyl methyl group. The peak at 4.3 ppm (h) represents the hydrogen atom on the methylene group, indicating that the methyl group in the polymer has been replaced by a bromine atom, thus confirming the success of the bromomethylation reaction. At the same time, the chemical shift and integral ratio of the hydrogen atoms in the spectrum are consistent with the target product.
[0074] Example 2
[0075] Trialdehyde phloroglucinol (208 mg, 1 mmol) and 5,5'-diamino-2,2'-bipyridine (279 mg, 1.5 mmol) were dissolved in 20 mL of N,N-dimethylaniline / 1,2-dichlorobenzene mixed solution (1:1 v / v), placed in a 50 mL Teflon-lined autoclave, and ultrasonicated for 5 min to make it uniformly dispersed. Then, 2.7 mL of 6 mol L -1 The mixture was stirred with a magnetic stirrer for 2 h, sealed, and heated to 120 °C for 72 h.
[0076] The precipitate was collected by centrifugation, washed with anhydrous tetrahydrofuran (6×4 mL) and acetone (3×4 mL), respectively, and dried under vacuum at 80°C overnight to obtain orange-red COF-TpBpy with a yield of 65%.
[0077] The prepared COF-TpBpy was ground into powder and dispersed in 50 mL of dimethylformamide solvent to form a suspension. The suspension was crushed by an ultrasonic cell disruptor at a power of 150 W for 2 h. During this period, the ultrasonic on / off time was set to 2 s and 3 s respectively, and the suspension was circulated and cooled to keep the suspension temperature at about 30 °C.
[0078] The suspension was vacuum filtered, washed with methanol (15×3 mL), and dried overnight at 80° C. to obtain a finer orange-red SLCOF-TpBpy powder.
[0079] Example 3
[0080] Weigh 30 mg of dried SLCOF-TpBpy, disperse it in 2 mL of N-methylpyrrolidone under argon protection, condense it to 0 °C in a cycle, add iodomethane (2.13 g, 15 mmol) dropwise, and react at room temperature for 24 h in the dark.
[0081] After the reaction was completed, the product was washed with methanol (15×3 mL) and dried in a vacuum drying oven at 80°C overnight to obtain the product QAmSLCOF-TpBpy.
[0082] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of N-methylpyrrolidone and ultrasonicated for 5 min to obtain a homogeneous solution.
[0083] QAmSLCOF-TpBpy (2.5% by weight of the mixed membrane solution) was weighed and dispersed in the above homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 h, a mixed membrane solution was obtained.
[0084] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as QAmSLCOF-TpBpy@PPO.
[0085] Example 4
[0086] 30 mg of dried SLCOF-TpBpy was weighed and dispersed in 2 mL of N-methylpyrrolidone under argon protection, and iodopropane (2.55 g, 15 mmol) was added dropwise and reacted at room temperature for 24 h.
[0087] After the reaction was completed, the product was washed with methanol (15×3 mL) and dried in a vacuum drying oven at 80°C overnight to obtain the product QAprSLCOF-TpBpy.
[0088] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of N-methylpyrrolidone and ultrasonicated for 5 min to obtain a homogeneous solution.
[0089] QAprSLCOF-TpBpy (2.5% by mass of the mixed membrane solution) was weighed and dispersed in the above homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 h, a mixed membrane solution was obtained.
[0090] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as QAprSLCOF-TpBpy@PPO.
[0091] Example 5
[0092] Weigh 30 mg of dried SLCOF-TpBpy, disperse it in 1 mL of dimethylformamide under argon protection, condense it to 0 °C in a cycle, add 11.75 g of 25% trifluoroiodomethane aqueous solution (15 mmol) dropwise, and react at 30 °C for 24 h in the dark.
[0093] After the reaction was completed, the product was washed with methanol (15×3 mL) and dried in a vacuum drying oven at 80°C overnight to obtain the product QAF3SLCOF-TpBpy.
[0094] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of dimethylformamide and ultrasonicated for 5 min to obtain a homogeneous solution.
[0095] QAF3SLCOF-TpBpy (2.5% by mass of the mixed membrane solution) was weighed and dispersed in the above homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 h, a mixed membrane solution was obtained.
[0096] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as QAF3SLCOF-TpBpy@PPO.
[0097] Comparative Example 1
[0098] Under argon protection, polyphenylene ether (1.8 g, 15 mmol, Mn = 50000-58000), N-bromosuccinimide (1.3623 g, 7.65 mmol) and azobisisobutyronitrile (0.0753 g, 0.46 mmol) were dissolved in 28 mL of chlorobenzene and refluxed at 135 °C for 6 h.
[0099] After the reaction solution cooled to room temperature, it was slowly added dropwise into 20 mL of methanol with continuous ultrasound to precipitate the reactants to prevent agglomeration.
[0100] The precipitate was washed repeatedly with methanol (10×4 mL), and the washed product was placed in a 50° C. forced air drying oven and dried overnight to obtain brominated polyphenylene ether (BPPO), and the detected bromination rate reached 40-50%.
[0101] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of bromination functional group) was dissolved in 10 ml of N-methylpyrrolidone, and ultrasonicated for 5 min to obtain a homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction, and a membrane solution was obtained after reacting for 24 h.
[0102] The membrane solution was poured into a clean culture dish and slowly dried at 80° C. to prepare a quaternary ammonium polyphenylene ether anion exchange membrane, which was denoted as QAPPO.
[0103] The prepared QAPPO anion exchange membrane was analyzed by nuclear magnetic resonance and the results showed that Figure 2 The hydrogen spectrum is shown. Figure 1 compared to, Figure 2 QAPPO in the medium showed new characteristic peaks, indicating structural differences, especially the unique peaks of QAPPO with nitrogen cations (N + ) appeared at 3.1ppm, and the chemical shift and integral ratio of the hydrogen atoms in the spectrum were consistent with those of the target product.
[0104] Comparative Example 2
[0105] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of N-methylpyrrolidone and ultrasonicated for 5 min to obtain a homogeneous solution.
[0106] 2.5% of the mass of the mixed membrane solution of SLCOF-TpBpy was weighed and dispersed in the above homogeneous solution, and trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 hours, a mixed membrane solution was obtained.
[0107] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as SLCOF-TpBpy@PPO.
[0108] Comparative Example 3
[0109] 30 mg of dried SLCOF-TpBpy was weighed and dispersed in 2 mL of N-methylpyrrolidone under argon protection. The mixture was condensed to 0 °C in a circulating manner, and iodopentane (2.97 g, 15 mmol) was added dropwise. The mixture was reacted at room temperature in the dark for 24 h.
[0110] After the reaction was completed, the product was washed with methanol (15×3 mL) and dried in a vacuum drying oven at 80°C overnight to obtain the product QApSLCOF-TpBpy.
[0111] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of N-methylpyrrolidone and ultrasonicated for 5 min to obtain a homogeneous solution.
[0112] QApSLCOF-TpBpy (2.5% by weight of the mixed membrane solution) was weighed and dispersed in the above homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 h, a mixed membrane solution was obtained.
[0113] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as QApSLCOF-TpBpy@PPO.
[0114] Comparative Example 4
[0115] Weigh 30 mg of dried SLCOF-TpBpy, disperse it in 2 mL of dimethylformamide under argon protection, condense it to 0 °C in a cycle, add heptafluoro-5-iodopentane (4.86 g, 15 mmol) dropwise, and react at room temperature at 40 °C for 30 h in the dark.
[0116] After the reaction was completed, the product was washed with methanol (15×3 mL) and dried in a vacuum drying oven at 80°C overnight to obtain the product QAF7SLCOF-TpBpy.
[0117] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of dimethylformamide and ultrasonicated for 5 min to obtain a homogeneous solution.
[0118] QAF7SLCOF-TpBpy (2.5% by mass of the mixed membrane solution) was weighed and dispersed in the above homogeneous solution. Trimethylamine (0.15 ml, 0.16 mmol) was added dropwise to carry out quaternization reaction. After reacting for 24 h, a mixed membrane solution was obtained.
[0119] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as QAF7SLCOF-TpBpy@PPO.
[0120] Figure 3 Shown are infrared spectra of COF-TpBpy frameworks with different microstructures, including SLCOF-TpBpy, QAmSLCOF-TpBpy, QAprSLCOF-TpBpy, QAF3SLCOF-TpBpy, QApSLCOF-TpBpy, and QAF7SLCOF-TpBpy. The common feature is the 1646 cm -1 and 1440cm -1 The peak at 1450-1350cm -1 The infrared spectral data in the range reflect the bending vibration of methyl and methylene groups, thus proving the successful grafting of carbon chains by quaternization reaction.
[0121] Figure 4 The infrared spectra of anion exchange membranes containing COF-TpBpy frameworks with different microstructures are given. Due to the low doping level of the ion channel QAxSLCOF-TpBpy, only the asymmetric vibration and symmetric vibration of the C=O bond in its molecule are clearly visible in the spectrum, corresponding to 1658cm -1 and 1711cm -1 The absorption peak at .
[0122] Application Example 1
[0123] IEC is closely related to ion conduction. The higher the IEC value, the more active groups in the material that can participate in ion exchange, which usually leads to higher ion conductivity. This is because more active groups can release and absorb ions, thereby promoting the migration of ions in the material.
[0124] This application example tests the IEC performance of different QAxSLCOF-TpBpy@PPO membranes, including the anion exchange membranes QAmSLCOF-TpBpy@PPO, QAprSLCOF-TpBpy@PPO and QAF3SLCOF-TpBpy@PPO prepared in Examples 3, 4 and 5, and the anion exchange membranes QAPPO, SLCOF-TpBpy@PPO, QApSLCOF-TpBpy@PPO and QAF7SLCOF-TpBpy@PPO prepared in Comparative Examples 1 to 4. The results are as follows: Figure 5 shown.
[0125] It can be seen that with the increase of the length of the quaternary ammonium alkyl chain of QAxSLCOF-TpBpy, the IEC values of different QAxSLCOF-TpBpy@PPO films show a gradually decreasing trend.
[0126] For QAmSLCOF-TpBpy@PPO with different simple alkyl grafting (2.07 mmol g -1 ), QAprSLCOF-TpBpy@PPO (2.03mmol g -1 ) and QApSLCOF-TpBpy@PPO (1.67 mmol g -1 ) membranes, the entanglement of long alkyl chains and the excessive hydrophobicity will hinder ion transport, proving the negative impact of this phenomenon on ion transport. However, compared with the original membrane QAPPO (1.96mmol g -1 ), IEC still has a certain degree of improvement, which proves that the grafting of moderate carbon chain length has a certain improvement effect on IEC.
[0127] In addition, although the IEC of fluorinated QAF3SLCOF-TpBpy@PPO is low due to its hydrophobicity, its 1.95mmolg -1 The IEC value is almost the same as that of the original membrane QAPPO (1.96mmol g -1 However, due to the longer carbon chain and the hydrophobicity of the fluorine-substituted groups, the IEC value of QAF7SLCOF-TpBpy@PPO dropped to the lowest value (1.63mmol g -1 ), demonstrating that carbon chain length plays a dominant role in ion transport efficiency.
[0128] The SLCOF-TpBpy@PPO membrane without quaternary ammonium modification did not provide more active sites, resulting in a decrease in the IEC value of the membrane to 1.85 mmol g -1 , which also indirectly proves the necessity of quaternary ammonium modification of COF-TpBpy framework materials in ion transport.
[0129] Application Example 2
[0130] The ionic conductivity of the QAxSLCOF-TpBpy@PPO membrane of the present invention was tested in a pure water electrolyte at a temperature range of 20 to 80°C. Figure 6 shown.
[0131] Figure 6 In the experiment, as the length of the alkyl chain of the quaternary ammonium reagent increases, its change pattern is almost consistent with the IEC trend, and the ionic conductivity also gradually decreases. Similarly, the ionic conductivity of QAmSLCOF-TpBpy@PPO and QAprSLCOF-TpBpy@PPO is worse than that of the original membrane QAPPO, but the QApSLCOF-TpBpy@PPO with a longer alkyl chain is worse than QAPPO. The ionic conductivity of the unmodified SLCOF-TpBpy@PPO is also inferior to that of QAPPO.
[0132] However, the fluorine-substituted QAF3SLCOF-TpBpy@PPO has the highest ionic conductivity of 65.54 ms / cm, which is 27.42 ms / cm higher than that of QAPPO (38.12 ms / cm). This is attributed to the fact that the fluorine groups help to increase the ion concentration of the AEMs material by reducing the hydration and expansion ratio, thereby improving the conductivity.
[0133] In contrast, although QAF7SLCOF-TpBpy@PPO also contains more fluorinated groups, the alkyl chain length is also greatly increased, which blocks the transmission of ions, once again proving that grafting with moderate carbon chain length should be the primary consideration in ion transport.
[0134] The above results prove that the quaternized QAxSLCOF-TpBpy of the present invention contains different lengths and structures. Its ordered ion transport pores and solid support structure enable it to be enriched in QAPPO, which to a certain extent solves the problem of low ion conductivity of AEMs. At the same time, under moderate carbon chain length, the channel structure of the fluorine-containing group can further enhance the ion conductivity by increasing the local microenvironment ion concentration, thereby improving the electrochemical performance of the battery.
[0135] Application Example 3
[0136] The water absorption and swelling rates of QAxSLCOF-TpBpy@PPO membranes, including QAmSLCOF-TpBpy@PPO, QAprSLCOF-TpBpy@PPO and QAF3SLCOF-TpBpy@PPO, which have improved ionic conductivity compared with QAPPO membrane, were further investigated. Figure 7 , Figure 8 shown.
[0137] Relying on the stability of the QAxSLCOF-TpBpy structure and the interaction between the phenyl ether side chain of the matrix membrane and the quaternary ammonium cation, the water absorption and swelling rate of QAmSLCOF-TpBpy@PPO and QAprSLCOF-TpBpy@PPO also showed a trend higher than that of the QAPPO membrane. Due to the hydrophobicity of fluorine atoms, the water absorption rate of the QAF3SLCOF-TpBpy@PPO membrane is almost the same as that of the QAPPO membrane, but the swelling rate is slightly lower. The results show that the anion exchange membrane prepared by the present invention has good dimensional stability, so that the membrane can maintain its morphological structure in a more severe environment.
[0138] Application Example 4
[0139] In addition, due to the poor compatibility of COF-TpBpy with polymers, it will affect the entanglement of polymer chains, resulting in stress concentration points where COF-TpBpy exists, resulting in an increased probability of breakage during stretching. The present invention can improve the mechanical properties of the film by processing multi-layer COF-TpBpy into a single-layer SLCOF-TpBpy.
[0140] Under argon protection, the prepared BPPO (0.21 g, containing 0.5 mmol of brominated functional group) was dissolved in 10 ml of dimethylformamide and ultrasonicated for 5 min to obtain a homogeneous solution.
[0141] Weigh 2.5% of the mass of the mixed membrane solution COF-TpBpy, grind the powder in a mortar until it is uniform, disperse it in the above homogeneous solution, add trimethylamine (0.15 ml, 0.16 mmol) dropwise for quaternization reaction, and react for 24 hours to obtain a mixed membrane solution.
[0142] The mixed membrane solution was poured into a clean culture dish and slowly dried at 80°C to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane, which was recorded as COF-TpBpy@PPO.
[0143] Mechanical properties of the above COF-TpBpy@PPO membranes, QAPPO and QAmSLCOF-TpBpy@PPO membranes were tested. Fig. 9 Tensile strength and elongation at break of different films are shown.
[0144] from Fig. 9 The results show that under the premise of consistent enrichment, the mechanical properties of QAPPO and QAmSLCOF-TpBpy@PPO do not change much, but the tensile strength of COF-TpBpy@PPO membrane drops sharply from 26.61MPa of QAPPO membrane to 10.26MPa.
[0145] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A covalent organic framework composite polyphenylene ether anion exchange membrane, which is an organic film composed of a quaternary ammonium polyphenylene ether represented by the following structural formula (I) as a film matrix and a COF-TpBpy framework grafted with an alkyl chain represented by the following structural formula (II) as a filler: ; The quaternized polyphenylene ether shown in the structural formula (I) is a copolymer QAPPO composed of quaternized polyphenylene ether structural units and polyphenylene ether structural units obtained by quaternization reaction of polyphenylene ether, and the molar ratio of the quaternized polyphenylene ether structural units is x =0.4~0.5; ; In the COF-TpBpy framework with alkyl chains grafted thereon as shown in the structural formula (II), R is C 1~3 Alkyl or fluorine-substituted alkyl.
2. The covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 1, characterized in that Film substrate The mass percentage is 95-99%, and the mass percentage of filler is 1-5%.
3. The covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 1, characterized in that The fluorine substitution is monofluorine substitution, polyfluorine substitution or perfluorine substitution.
4. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 1 is to dissolve the brominated polyphenylene ether represented by the structural formula (III) in a well-soluble solvent thereof, add a required amount of the COF-TpBpy framework grafted with an alkyl chain represented by the structural formula (II), introduce trimethylamine into the framework for quaternization reaction after uniform dispersion, and dry the reaction solution to form a film to prepare the anion exchange membrane: ; in, The brominated polyphenylene ether is a copolymer composed of brominated polyphenylene ether structural units and polyphenylene ether structural units, and the molar ratio of the brominated polyphenylene ether structural units is x =0.4~0.
5.
5. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 4, characterized in that The well-soluble solvent of the brominated polyphenylene ether is N-methylpyrrolidone or dimethylformamide.
6. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 4, characterized in that The reaction solution after the quaternization reaction was spread as a membrane and placed under vacuum at 80° C. for not less than 30 hours to prepare a covalent organic framework composite polyphenylene ether anion exchange membrane with a membrane thickness of 60±5 μm.
7. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 4, characterized in that The alkyl chain grafted COF-TpBpy framework shown in the structural formula (II) is prepared by using the covalent organic framework material COF-TpBpy as a raw material, and reacting the covalent organic framework material COF-TpBpy with an iodide of the structural formula RI in a benign dispersing solvent to obtain a COF-TpBpy framework grafted with alkyl chains of different structures, wherein R is C 1~3 The alkyl group or the fluorine-substituted alkyl group, wherein the fluorine-substituted group is monofluorine-substituted group, polyfluorine-substituted group or perfluorine-substituted group.
8. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 7, characterized in that The covalent organic framework material COF-TpBpy is an ion channel COF-TpBpy structure obtained by condensing trialdehyde phloroglucinol and 5,5'-diamino-2,2'-bipyridine as raw materials in an N,N-dimethylaniline / 1,2-dichlorobenzene solvent system of acetic acid aqueous solution.
9. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 8, characterized in that The molar ratio of trialdehyde phloroglucinol to 5,5'-diamino-2,2'-bipyridine is 1:1.5-2.
10. The method for preparing the covalent organic framework composite polyphenylene ether anion exchange membrane according to claim 8, characterized in that The covalent organic framework material COF-TpBpy is dispersed in a dimethylformamide or N-methylpyrrolidone solvent system to form a suspension, and the suspension is crushed and refined using an ultrasonic cell disruptor. After removing the solvent, a refined SLCOF-TpBpy material is obtained.
Citation Information
Patent Citations
Mixed matrix anionic membrane and manufacturing method thereof
CN109546191A
Preparation method of cation covalent organic framework nanofiltration membrane and application of cation covalent organic framework nanofiltration membrane in dye interception
CN118161991A
Covalent organic framework-based composite anion exchange membrane with high quaternary ammonium content and preparation method of covalent organic framework-based composite anion exchange membrane
CN118440486A